Studi Pemisahan Tugas Dan Fungsi Account Representative (Ar) Pengawasan Dan Konsultasi Dalam Pencapaian Target Penerimaan Pajak (Studi Kasus Pada Kantor Pelayanan Pajak Pratama Batu) - Perdana, Kurniawan Wira (Arthavidya Jurnal Ilmiah Ekonomi, 2018)
One of the changes in bureaucratic reform in taxationknown as the Modern Tax Administration System is theestablishment of Account Representative (AR) which has the task ofsupervision and consultation in achieving the target of tax revenue.In essence the role is mutually contradictory and often lead toconflict of interest on AR to its taxpayer. So that required separationof duty and function of AR.The purpose of this study are 1) To knowthe effectiveness of separation of Account Representative (AR)function on the task of Consultation and Supervision. 2) Knowing theimpact of the separation of functions on the realization of taxrevenues, 3) Knowing that the separation of duties of theConsultative and Supervisory functions effectively reduces theburden of responsibility of AR officers on contradictory tasks; 4)Knowing the better AR performance after the separation of taskfunctions Consultation and Supervision.This research is adescriptive research that is research method that try to describe andinterpret object according to what it is (Best, 1982 in Sukardi, 2003).This research is also often called noneksperimen because in thisstudy the research did not control and manipulation of researchvariables.The results showed that the separation of functions andduties Account Representative (AR) effectively improve theperformance of AR, as evidenced by the increasing compliance ofTaxpayer Small Tax Office of Batu in submitting Tax Report (SPT)and pay tax so that the tax target is achieved. The division of roleson AR tasks and functions will create simplification of function andservice tasks and supervision, so that AR performance increases withreduced workload. Each AR officer can work optimally. AR officerscan explore the potential of taxpayers so it is expected to increasetaxpayer compliance about the obligation to pay taxes.Key Word: tasks and functions, Account Representative (AR)